PENERAPAN METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM PENGENDALIAN PERSEDIAAN PERLENGKAPAN OPERASIONAL PADA FLOBAMORA BARBERSHOP - Anselmus Labi; Desriana Sintha Lullung, Inggrid Hilda, Edwin Fernando, Christenson Vadelo, Anggun Parinding (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
Inventory management is a crucial aspect of operational management that determines cost efficiency and the smooth running of services in Micro, Small and Medium Enterprises (MSMEs). This study aims to apply the Economic Order Quantity (EOQ) method to determine the optimal order quantity, safety stock, reorder point, and to minimise total inventory costs at Flobamora Barbershop, Jayapura. This study employs a descriptive quantitative approach using primary data obtained through observation and interviews, as well as secondary data from business records. The results indicate that previous inventory management was conventional and based on estimates, resulting in high inventory costs of idr12,210,000 per year. Using the EOQ method, the most economical order quantities were determined to be 13 packs of neck towels, 134 bottles of pomade, 95 bottles of styling cream, and 80 razor blades. The application of this method proved effective in reducing total inventory costs to idr5,200,550 per year, representing a saving of 57.41% (idr7,009,450). Furthermore, the establishment of safety stock levels and reorder points ensures the availability of operational goods and prevents the risk of stock shortages when serving customers. The EOQ method is highly suitable for implementation as it balances ordering and storage costs, whilst improving operational efficiency.